Oportunistyczny model pracy socjalnej ze skazanymi - Stępniak, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The study focuses on a critical analysis of the rehabilitation model implemented in the context of the sentence of imprisonment. Opposite the indicated form of judicial enforcement of sentence lies social work. Realistically perceived process of execution of the penalty should assume the initiation of activities related to social empowerment of prisoners, prevention of deterioration of their social skills and provision of contact with the outside world. From this perspective, a personalized social rehabilitation should be treated as a rather ineffective undertaking.
Keywords: praca socjalna; rehabilitacja; kara pozbawienia wolności